PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI DINAMIKA MOTOR TASIKMALAYA - Sudiarti, Sri (STIBANKS Al Ma'soem Bandung, 2018)
The purpose of this research is to know and analyze about the influence of Service Quality to Consumer Satisfaction in DinamikaMotorTasikmalaya.The type of research used is Verifier Verifikatif. The research method used in this research is survey method, while data collection technique is done through questioner and interview. Respondents are taken as many as 100 respondents viewed from the number of population (consumers) who come per day. The analysis tool used is simple regression analysis and t test.The results showed that the Quality of Service in Dinamika Motor Tasikmalaya good, as well as customer satisfaction Tasikmalaya Motor Dinamika including good. Service quality positively affects customer satisfaction in Dinamika Motor Tasikmalaya.